Field notes contributed by Peter C. Petersen, fall 1991 - Petersen, Peter C.et al (1991)
List of birds and locations contributed by Peter C. Petersen with observers Mary Lou Petersen, Ann M. Barker, Randall Pinkston and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed